Flubendazole, FDA-approved anthelmintic, elicits valid antitumor effects by targeting P53 and promoting ferroptosis in castration-resistant prostate cancer. (February 2021) - Zhou, Xumin; Zou, Libin; Chen, Wenbin; Yang, Taowei; Luo, Junqi; Wu, Kaihui; Shu, Fangpeng; Tan, Xiao; Yang, Yu; Cen, Shengren; Li, Chuanyin; Mao, Xiangming
Graphical abstract: Highlights: Flubendazole, a FDA-approved anthelmintic, may be effective in treating Castration-resistant Prostate Cancer. Flubendazole inhibits the cell viability in vitro and tumor growth of Castration-resistant Prostate Cancer in vivo. Flubendazole exhibits a synergistic effect with 5-fluorouracil (5-Fu) in chemotherapy of CRPC in vitro and in vivo. Flubendazole promotes the Ferroptosis by targeting P53 protein in Castration-resistant Prostate Cancer cells. Abstract: On account of incurable castration-resistant prostate cancer (CRPC) inevitably developing after treating with androgen deprivation therapy, it is an urgent need to find new therapeutic strategies. Flubendazole is a well-known anti-malarial drug that is recently reported to be a potential anti-tumor agent in various types of human cancer cells. However, whether flubendazole could inhibit the castration-resistant prostate cancer has not been well charified. Thus, the aim of the present study was to characterize the precise mechanism of action of flubendazole on the CRPC. In this study, we investigated the potential effect of flubendazole on cell proliferation, cell cycle and cell death in CRPC cells (PC3 and DU145). We found that flubendazole inhibited cell proliferation, caused cell cycle arrest in G2/M phase and promoted cell death in vitro, and suppressed growth of CRPC tumor in xenograft models. In addition, we reported that flubendazole induced the expression of P53, which partly accounted for the G2/M phase arrest and led to inhibition of the transcription of SLC7A11, and then downregulated the GPX4, which is a major ferroptosis-related gene. Furthermore, flubendazole exhibited synergistic effect with 5-fluorouracil (5-Fu) in chemotherapy of CRPC. This study provides biological evidence that flubendazole is a novel P53 inducer which exerts anti-proliferation and pro-apoptosis effects in CRPC through hindering the cell cycle and activating the ferroptosis, and indicates that a novel utilization of flubendazole in neoadjuvant chemotherapy of CRPC.